Aspek Hukum Perjanjian Sewa Beli - Devayanti Dewi, Ni Komang; Wiryawan, I Wayan (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014, 2014)
In a hire purchase agreement does not rule out the possibility that the lease buyer for any reason, unable to meet its obligations to pay rent in accordance with the agreement that has been agreed with the seller that he ( the buyer ) can be categorized has done a broken promise or breach of contract . The purpose of this paper is to investigate the Legal Aspects of Hire Purchase Agreement . Study is a normative legal research is a study of secondary data (data library ) . That is by reading , studying and describing the norm - the norm of law and article - article and the opinions of experts in connection with a lease issues . In a lease agreement setatus ownership of the new goods move from the lease seller to the buyer after the entire amount of the rental price of the goods paid in full . In a lease agreement seemed no delays title to the goods until the rest of the last installment is paid off by the buyer leases . Legal consequences for debtors in default if it was going to get penalties or criminal sanctions in the form of compensation payments made by the debtor for losses that have been suffered by creditors ( Article 1243 of the Civil Code ) , the engagement may be canceled by the creditors through a court decision to pay compensation where the risk of switching to borrowers since the event of default.
Keywords: Aspect, Legal Agreements, Hire Purchase